2006
DOI: 10.2190/f143-5363-3442-5163
|View full text |Cite
|
Sign up to set email alerts
|

The Life Tape Project: Increasing Family Social Support and Symbolic Immortality with a Brief Existential Intervention for Cancer Patients and Their Families

Abstract: Cancer poses a powerful threat to the emotional equilibrium of patients and their families. A key role of the family and medical team is to provide a supportive environment as the patient confronts the reality of death. Few interventions have been developed to help families support patients in dealing with fears of death and dying. We present one such approach, the Life Tape Project (LTP), that helps bring families closer together, increases communication, and acts as an existential intervention leading to gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…It helped relatives to respond to their sense of helplessness and loss when a loved one is facing death. This may contribute to how they manage to handle the existential anxiety about their own mortality [33]. …”
Section: Support When Death Is Nearmentioning
confidence: 99%
“…It helped relatives to respond to their sense of helplessness and loss when a loved one is facing death. This may contribute to how they manage to handle the existential anxiety about their own mortality [33]. …”
Section: Support When Death Is Nearmentioning
confidence: 99%
“…16,28,29 Results While in total, 5 interventions described in 24 publications fulfilled the inclusion criteria and were included in this review, many interventions identified during the literature search did not fulfill the inclusion criteria. Exclusions involved not being structured by time and/or content, 30-47 not being focused on palliative care or exclusively focused on bereavement, 48-71 focused on early-stage cancer [72][73] or recurrent breast cancer, 74 not including minor children/parents, [75][76][77][78] or not being evaluated in an empirical study [79][80][81][82][83] (listed regarding first inclusion criterion that did not fit). For reasons and corresponding numbers of exclusions dependent on the stage of the process, see Figure 1.…”
Section: Inclusion Criteria and Assessment Of Study Qualitymentioning
confidence: 99%
“…Although the LTP was developed initially from clinical observation and judgment, the intervention is consistent with the broader research literature that affirms the role of social support in general, and family support in particular, in moderating the effects of cancer on patient psychological well-being. Preliminary findings from a pilot study (Rosenbaum et al, 2006) suggest that the LTP can help bring families closer together and improve communication and support. Additionally, patients reported gaining other benefits from their participation, including a greater sense of meaning, self-awareness, and identity, suggesting that they learned from and grew through the process.…”
Section: The Life Tape Projectmentioning
confidence: 99%
“…The patient is encouraged to express his or her feelings about all these issues, and friends and family are encouraged to share their memories and feelings about the impact the patient has had on their lives. The videotape is later edited by a technician in consultation with the interviewer to remove extraneous material (e.g., lighting adjustment, miscellaneous interruptions) and a free copy (VHS and/or DVD) is given to the patient as a permanent keepsake and legacy for the family (for further information, including an outline of the interview structure, see Rosenbaum, et al, 2006 or go to www.cancersupportivecare.com/Legacy/conduct.html.) Procedure A packet including a consent form and baseline pen-and-paper measures was mailed to each participant for completion during the week preceding the scheduled LT interview.…”
Section: Interventionmentioning
confidence: 99%